Juventude e educação: os sentidos do ensino médio na periferia do Distrito Federal - Condé, Ágatha Alexandre Santos (2016)
The objective of this research is to discuss the meanings of high school, with the use of ethnographic case study to analyze the everyday school life of young students from Ced 04 Sobradinho, in the suburb of the Federal District. This is to relate Youth and Education, considering the material aspects historically constructed in the community and at school. During the academic career of a class of 40 students, between 2013 and 2015, it was possible to follow the construction of the directions given to the last stage of basic education, whose social structure of class society, to which belong the subjects analyzed, it is crucial to educational duality that, in turn, competes with dynamic formation of youth identities - represented the territory and the body - to give meanings to high school. By identifying the school's place in the lives of students it is clearly perceived that the proposals contained in the regulatory documents of high school, especially LDB no. 9.394/96 and the High School Curriculum Guidelines, 2012, did not include in practice teaching with a view to the unit training, making students deal instrumentally with the school in search of high school conclusion and its certification or not reach success in continuation of their studies, higher education, or even do not feel prepared for the uncertainties and demands of the labor market. Of the 40 young people initially investigated, 27 finished high school, 9 were rejected in the final stage of basic education and 4 students left school. None of the graduating youths has achieved a place in higher education at the public university.